Integrated IT performance management - Bainey, Kenneth R. (Taylor & Francis, a CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T&F Informa, plc, 2016)
Presenting a compilation of the author's extensive IT management, performance management, project management, enterprise architecture, and applications development knowledge and skills, and over 30 years of industry experiences, this book provides valuable insights to functional and executive managers (business and IT) in their search for the elusive or magical "silver-bullet" solution to performance management